PENGEMBANGAN SISTEM MANAJEMEN KOST BERBASIS WEBSITE UNTUK MENINGKATKAN EFISIENSI PENGELOLAAN DAN PROMOSI PROPERTI KOST - I Gede Dhananjaya (Yayasan Lavandaia Dharma Bali, 2025)
The utilisation of technology in property management for boarding houses has become an effective solution to address the challenges of managing an increasing amount of tenant data. Our partner had been using Excel to manage boarding house data, which required manual input, prone to errors, difficult to update in real-time, and inefficient for archiving and information retrieval. These shortcomings often led to data inaccuracies and longer processing times, especially as the number of tenants and rooms increased. As a solution, this research developed a web-based boarding house management system that not only facilitated automatic and structured data management but also provided digital promotion features to expand the reach of boarding house information to potential tenants. This system was designed using the waterfall method, with Laravel as the main framework for backend development, supported by React.js and Inertia for the system's front-end development, and SQL as the database. Testing results have shown that this system is capable of overcoming the weaknesses of manual methods such as repetitive data entry and error susceptibility, while significantly improving the efficiency of boarding house management and marketing.